Youth unemployment saga in Nigeria: implications for security challenges and economic development - E.O, MOFOLUWAWO (Advances in Social Sciences Research Journal, 2015)
The paper examined the challenge of youth unemployment in Nigeria and its implications for security and economic development. The paper adopted descriptive survey method. A total of 200 subjects were drawn through random sampling techniques across public servants, students and youths in Ogbomoso township of Oyo State, Nigeria. The research questions were analyzed with the use of mean score and standard deviation. The result of the study among others revealed that lack of power supply, lack of practical entrepreneurial skills and mass production of graduates from secondary and tertiary institutions are the causes of unemployment. The implication of these has led to increased social vices, rise in religious riots and militancy, vandalism and destruction of lives, slow pace of economic development and high waste of human resources. Thus, it was recommended that crops and livestock farming should be made attractive through the provision of incentives to young graduates who may wish to go into crop and livestock farming. Entrepreneurship should be drafted into Nigeria’s school curricular and made compulsory for all levels in secondary and tertiary institutions of learning. This will infuse the spirit of enterprise, perseverance and merit into the youths as opposed to the quick-quick and now-now syndrome that has overtaken the nation.